ANALYSIS OF MATHEMATICAL RESOLUTION REVIEWED FROM COGNITIVE STYLE AND MATHEMATICAL ANXIETY OF STUDENTS IN STUDENTS OF CLASS VII SMP FRATER MAKASSAR - S, Silvester (Global Science Education Journal, 2019)
This study aims to 1) description of the mathematical problem solving in terms of cognitive style field-independent (FI) mathematical anxiety and low and high, 2) description of mathematical problem solving in terms of cognitive style field-dependent (FD) and mathematical low and high anxiety. Type a descriptive qualitative research. Instrument and data collection that is used in the form of Test anxiety now, GEFT, math test and interview. Data analysis techniques used, namely the reduction of data, data presentation, data verification and withdrawal of the conclusion. Research results: 1) the stylish Subject of cognitive ability in resolving the problem FI i.e. analytical and clear, but there is confusion on step completion caused high anxiety. 2) FD Subject in resolving problems i.e. thorough thinking because anxiety low was able to complete the issue hadn't yet high anxiety while still think dabble so can not solve the problem completely. 3) link between cognitive style and anxiety seen in a mathematically solve problems I on righteousness calculations and measures penyelesainnya. While the mathematical anxiety cognitive style is influenced by the FI and FD is seen in resolving problems, a subject that has broad perceptions of analytic and so was able to resolve the problem, while the subject is more intuitive, FD presepsi narrow and unable to resolve the problem completely